CONTACT SENSITIZATION TO METALS AMONG A GROUP OF BULGARIAN DENTAL TECHNICIAN STUDENTS IN RELATION TO THE DURATION OF THEIR EDUCATIONAL EXPOSURE - Maya Lyapina; Todor Kundurjiev; Karolina Lyubomirova (Peytchinski Publishing, 2021)
Purpose: Sensitization to metals is a significant problem in dental, occupational exposures. The purpose of this study was to evaluate the prevalence of contact sensitization to selected metals during the course of study among students from dental technician school and the prevalence of co- sensitization. Material and Methods: Skin patch testing with potassium dichromate, cobalt, gold, nickel, copper, palladium, aluminium, tin and sodium tetrachloropalladate(II)hydrate was performed among 150 dental technician students (38 - 1st year of study,40 - 2nd year of study and 38 - 3rd year of study); the control group included 34 students without educational exposure to metals. Chi-square test, Fisher Exact Test and multiple binary logistic regression were used in data analysis. Results: During the educational course of dental technician students, a clear tendency of increase in the prevalence of sensitization to nickel (1st year of study - 10.5%, 3rd year of study - 36.8% cobalt (13.2% vs 39.5%) and palladium(II)chloride (10.5% vs 26.3%) was established. For the whole studied population, the prevalence of positive reactions to sodium tetrachloropalladate (II) hydrate was the highest - 30%; the highest recorded value was among the 2nd year students - 57.5%. The prevalence of sensitization to more than one metal allergen among the studied population was high (66.7%), the highest value was reported among 3rd-year dental technician students (78.9%). Conclusions: Our data indicate a high risk of contact sensitization to metals relevant for the dental technician students, which increases in the course of educational exposure for some of the metal haptens. Sodium tetrachloropalladate(II) hydrate could be outlined as a sensitizer of prominent importance, probably due to the increased sensitivity of this test salt. Additional and studies, including more respondents from the othe Colleges in Bulgaria are recommended. Adequate prevention programs and information should be provided, and the European Union regulations should be properly applied.